2012
DOI: 10.1089/vbz.2012.0965
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Aorta in Brucellosis: The Forgotten, Life-Threatening Complication. A Systematic Review

Abstract: Human brucellosis is a disease of protean manifestations, and has been implicated in complications and focal disease in many human organ systems. However, little is collectively known about the background, the course, the clinical characteristics, the diagnostic issues raised, and the short- and long-term therapeutic approaches in patients with aortic involvement as a complication of brucellosis. With the aim to glean from the literature useful information to better understand and manage this complication, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 46 publications
3
33
0
Order By: Relevance
“…The findings described in these studies are consistent with the observations recently made by Prado-Calleros and colleagues who identified 480 cases in a systematic literature review [1]. Lessons to be learned from the studies described here include the high incidence of S. aureus as a cause of descending mediastinitis in infants and, to a lesser extent, in adults, as well as the higher frequency of anaerobic infection in the latter group.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The findings described in these studies are consistent with the observations recently made by Prado-Calleros and colleagues who identified 480 cases in a systematic literature review [1]. Lessons to be learned from the studies described here include the high incidence of S. aureus as a cause of descending mediastinitis in infants and, to a lesser extent, in adults, as well as the higher frequency of anaerobic infection in the latter group.…”
supporting
confidence: 91%
“…A review of brucellar aortitis published in 2012 identified 46 cases with 18 having involvement of the ascending aorta; with 16 of the 18 had aortic valve endocarditis [1]. Of note is that the infection was complicated by the presence of lumbar spondylodiscitis in 13/30 whose vascular infection involved the descending thoracic or abdominal aorta; 12 of the 13 had abdominal aortitis.…”
mentioning
confidence: 99%
“…The most commonly cultured organisms include Staphylococcus (30%), Streptococcus (10%) and Salmonella (10%) 1–4. Other microorganisms such as Brucella can be responsible for aortitis 5 . C. fetus is a very rare cause of mycotic aneurysm especially in the elderly with other underlying pathologies 3.…”
Section: Discussionmentioning
confidence: 99%
“…2 This complication involved the ascending thoracic aorta in 18 cases (in 16 of them as a consequence of brucellar endocarditis), and the descending thoracic aorta or the abdominal aorta in the remaining 30 cases. In the latter, it was associated with spondylitis of the lumbar spine in 13 cases.…”
mentioning
confidence: 99%
“…Actually, in a recent paper appeared on PubMed in October 2012: we analyzed the epidemiologic and clinical characteristics of 46 cases of brucellar aortic involvement. 2 This complication involved the ascending thoracic aorta in 18 cases (in 16 of them as a consequence of brucellar endocarditis), and the descending thoracic aorta or the abdominal aorta in the remaining 30 cases. In the latter, it was associated with spondylitis of the lumbar spine in 13 cases.…”
mentioning
confidence: 99%